An overview of attention-deficit hyperactivity disorder in the pediatrics - Alzamzami, Abdulghani A.; Alfadhel, Ali F.; Alsuhayib, Mahmood A.; Alshibli, Musaad A.; Abdullah, Saad A.; Muharraq, Ahlam M.; Alkhaldi, Abdulelah S.; Alrumman, Sarah N.; Alshawi, Maha E.; Alshawi, Maha E.; Nagadi, Kholoud K.; Alsalhat, Saleh A. (International Journal Of Community Medicine And Public Health, 2023)
Attention-deficit hyperactivity disorder (ADHD), which is a disorder affecting children worldwide, has lasting effects on their behavior and cognitive functions. This review will explore the complexities of ADHD in children, including its classification, manifestations and management strategies. We will discuss the subtypes of ADHD and how they present challenges in various aspects of a child's life. From difficulties with attention to hyperactivity and impulsivity these subtypes have profiles that impact academic performance, social interactions and emotional regulation. The symptoms of ADHD intertwine inattentiveness, hyperactivity, impulsivity, emotional instability and academic struggles in patients. These symptoms significantly affect a child's functioning across areas such as schoolwork, social life and emotions. To effectively manage ADHD in children requires an approach that combines medication options with interventions, educational support systems tailored to individual needs and parental support programs that emphasize collaboration between healthcare professionals and families. This comprehensive approach seeks to address the requirements of children dealing with ADHD. Its goal is not to reduce symptoms but to improve their long-term outcomes and overall quality of life. By explaining the nature of ADHD in children, this analysis aims to provide an understanding of the disorder. It highlights the significance of customized interventions, early detection, and continuous support in order to enhance the well-being and developmental path of affected children.